The prevalence and clinical presentation of antenatal depression in rural South Africa - Rochat, Tamsen Jean; Tomlinson, Mark; Bärnighausen, Till; Newell, Marie-Louise (Journal of affective disorders, 2011)
Although the prevalence of depression is similar in pregnant, postpartum and non-pregnant women, the onset of new depression is higher during the perinatal period. Women of low-income, and those living in low and middle income countries, are known to be at particularly high risk. Early identification and treatment of antenatal depression may improve pregnancy outcomes and could serve as an early indicator of postnatal depression. Culturally sensitive and accurate diagnostic tools are urgently needed. A consecutive series of 109 pregnant women were recruited in the third trimester at a primary health clinic, in a rural part of South Africa, with a high HIV prevalence. A cross sectional assessment of depression was completed using a structured clinical interview method and DSM-IV diagnostic criteria. Qualitative data on women's descriptions of depressive symptoms was also collected. The aim was to examine the prevalence of depression and to better understand the presentation of depressive symptomatology in this population. Prevalence of depression was high, 51/109 (47%), with over half of the depressed women 34/51(67%) reporting episode duration greater than two months. 8/51 reported a prior history of depression. Women used psychological language to describe symptoms and, as a result, standardised diagnostic tools were culturally sensitive. Somatic pregnancy symptoms were frequently reported, but did not overestimate depression. Both HIV positive (27/51) and HIV negative (24/51) women were at risk of being depressed. The study is limited by the small sample size and possible attrition biases. Antenatal depression is high and clinical presentation is similar to high income countries. Standardised diagnostic tools are culturally sensitive and adequate for early detection.